Household Level Assessment of Climate Change Vulnerability of North Bank Plains Zone Farmers of Assam - Chetri, Trilochan Karki; Das, Pabitra Kr.; M, Misha Madhavan; Barman, Indrajit; Saikia, Dipankar (Indian Journal of Extension Education, 2021)
The study was carried out to assess the vulnerability of farmers to climate change in north bank plains zone of Assam. For this 2 districts were selected randomly from the north bank plains zone of Assam i.e., Sonitpur and Udalguri. A household level survey was carried out with the selected farmers to obtain the primary data. For this, total 120 farmers were selected from 6 different villages through proportionate random sampling. Vulnerability index was worked out by considering 10 different indicators. Findings revealed that 69.17% of farmers belonged to medium vulnerability category followed by 16.67 % and 14.17% in high and low vulnerability category respectively. The mean vulnerability score was 0.455 indicating that, on an average, respondents had medium vulnerability to climate change. Most of the respondents are belonged to medium category.Â